CITRA DIFABELITAS DALAM KARYA RATNA INDRASWARI IBRAHIM - Mansurudin, susilo (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2016)
Abstract. Injustice has been part of life for different ability people, especially for diffabled women in many parts of Indonesia. A diffabled woman writer, Ratna Indraswari Ibrahim, refuses the assumption and proves on strength and spirit of life in women and diffable people through her works. This study discusses Ibrahim’s short stories about women and the life of her diffabled characters. The data sources of the study are novelettes by Ratna Indraswari Ibrahim. The data are quotes from the works that talk about diffability. The study was based on understanding and interpretation processes. The study found that the Ibrahim’s works discusses the image and strength of the diffabled woman character in defending for her rights. Ibrahim also proves that being diffabled does not necessarily mean constant mercy-seeking and dependence on others. Ibrahim tries to introduce a new paradigm that the diffabled people have the same pontential as the normal people do. The image of diffability is illustrated in her works that are fully loaded with struggle of both a woman and a diffabled person. Kata kunci: citra, difabel, Ratna Indraswari Ibrahim